Hypoxia Promotes Tumor Growth in Linking Angiogenesis to Immune Escape - CHOUAIB, Salem; MESSAI, Yosra; COUVE, Sophie; ESCUDIER, Bernard; HASMIM, Meriem; NOMAN, Muhammad Z. (Frontiers in Immunology, 2012)
Despite the impressive progress over the past decade, in the field of tumor immunology, such as the identification of tumor antigens and antigenic peptides as potential targets, there are still many obstacles in eliciting an effective immune response to eradicate cancer. It has become increasingly clear that tumor microenvironment plays a crucial role in the control of immune protection and contains many overlapping mechanisms to evade antigen specific immunotherapy. Obviously, tumors have evolved to utilize hypoxic stress to their own advantage by activating key biochemical and cellular pathways that are important in progression, survival and metastasis. Among the hypoxia-induced genes, hypoxia-inducible factor (HIF-1) and vascular endothelial growth factor (VEGF) play a determinant role in promoting tumor cell growth and survival. In this regard, hypoxia is emerging as an attractive target for cancer therapy. How the microenvironmental hypoxia poses both obstacles and opportunities for new therapeutic immune interventions will be discussed.